Effect Of Gamma Irradiation on Yield and Quality of Guar (Cy A Mopsis Tetragonoloba ) L. Taub. - Chaudhary, M S; Ram, Het; Hooda, R S; Dhindsa, Kuldip Singh (Annals of Arid Zone, 2016)
The seeds of guar (Cymopsis tetragonoloba L. Taub.)were irradiated with 2,5, 10, 15 and 20 Kr doses of gammarays and the X2 population was raised at the ResearchFarm of Haryana Agricultural University Hissar. Investigationswere made to study the effect of irradiation ongrain Yield and its protein and gum contents. Yield perplant has been found to increase with increasing doses ofgamma rays. Similar trend has been observed for proteincontent of the grains. The gum. content was also higherin all the gamma ray treatments as compared to control.